Global Marketing Success: Market Orientation, Innovation, Competitive Advantage: Sukses Pemasaran Global: Orientasi Pasar, Inovasi Produk, dan Keunggulan Kompetitif - Iin Aniyati; Lilik Indayani (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the relationships between market orientation, product innovation, competitive advantage, and marketing performance in a global context. Using the Slovin method, a sample of 251 respondents was collected to analyze primary data through Partial Least Squares (PLS). The findings highlight that market orientation positively affects competitive advantage and marketing performance, while product innovation positively influences both competitive advantage and marketing performance. Moreover, competitive advantage serves as a mediator between market orientation and marketing performance, as well as between product innovation and marketing performance. These results emphasize the strategic significance of market orientation, product innovation, and competitive advantage in achieving superior marketing performance in a competitive global marketplace. The implications suggest that firms should prioritize developing market orientation, fostering product innovation, and leveraging competitive advantage to enhance their marketing performance in the global context. Highlights: Market orientation and product innovation positively influence competitive advantage and marketing performance. Competitive advantage acts as a mediator between market orientation and marketing performance, as well as between product innovation and marketing performance. Emphasizing market orientation, fostering product innovation, and leveraging competitive advantage are crucial for achieving marketing success in a global context. Keywords: Market orientation, Product innovation, Competitive advantage, Marketing performance, Global context